Final report on the CARICOM-IDB Project ATN/SF-7075-RG : support for the implementation of WTO commitments in the Caribbean Community (CCS GeorgetownGY, 2005)
Reports on the diagnostic studies that were prepared to outline the status of, and recommended actions to support the implementation of CARICOM countries commitments. Deals with capacity-building activities in three priority areas viz. technical barriers to trade; customs valuation and services. Presents a best practices report describing some of the approaches adopted by certain countries in the implementation of their WTO commitments.
Keywords: TRADE